Self-regulated learning: A key factor in the effectiveness of online learning for second language learners - Yu, Bo (Frontiers in Psychology, 2023)
With the further development of Internet technology, online learning has become an important way for learners in the digital age. As an important learning strategy, self-regulated learning plays an important role in e-learning. Whether learners can succeed in the network learning environment largely depends on their online self-regulating learning ability. This research reviews the theories and models of self-regulated learning, and analyzes the influences of individual factors and external factors on second language self-regulated learning in the online learning environment. And some implications in learning and teaching are given, as well as suggestions for future research.